2023
DOI: 10.1371/journal.pone.0285614
|View full text |Cite
|
Sign up to set email alerts
|

Types and anatomical locations of injuries among mountain bikers and hikers: A systematic review

Paul John Braybrook,
Hideo Tohira,
Tanya Birnie
et al.

Abstract: Background Mountain biking and hiking continue to grow in popularity. With new participants to these sports, it is likely the number of injuries will increase. To assist medical personnel in the management of these patients we attempted to quantify the types and locations of injuries sustained by mountain bikers and hikers. Objective The objective of this systematic review is to identify the type and anatomical location of injuries for both mountain bikers and hikers. Methods A systematic search was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Understanding ground reaction force and GRF patterns may also facilitate the implementation of intervention programs to improve weight distribution and reduce joint stress, thus alleviating asymmetries or excessive joint loading. This would be particularly important in the prevention of musculoskeletal injuries resulting from frequent and prolonged walking on various surfaces, such as blisters [67] and ankle sprains [68]. Likewise, COP data may allow for the design of exercises that specifically target balance deficits and enhance overall stability.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding ground reaction force and GRF patterns may also facilitate the implementation of intervention programs to improve weight distribution and reduce joint stress, thus alleviating asymmetries or excessive joint loading. This would be particularly important in the prevention of musculoskeletal injuries resulting from frequent and prolonged walking on various surfaces, such as blisters [67] and ankle sprains [68]. Likewise, COP data may allow for the design of exercises that specifically target balance deficits and enhance overall stability.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Studies have shown that cyclists are not immune to injury or illness. [2,[17][18][19][20][21] The range of injuries and illnesses that do occur is vast, however, the reporting of injuries varies signi cantly with a signi cant lack of homogeneity between studies and disciplines. [2,4] Injury and Illness surveillance studies in other sports are far more advanced and have seen the development of speci c warm-up routines to reduce injury risk such as FIFA 11 [22]in soccer, and Gaelic Athletic Association (GAA) 15 [23] in Gaelic games.…”
Section: Search Strategymentioning
confidence: 99%